Analisis Gaya Kepemimpinan Kepala Sekolah Yang Ideal - Fitriyani, Fitriyani; Aidil, Aidil; Zainab, Zainab (El-Ghiroh : Jurnal Studi Keislaman, 2021)
Principal leadership is one of the factors that can encourage schools to be better. The leadership in question is leadership with the ideal type. In general, there are still schools whose leadership type is still not ideal. So that the school they lead is still not able to progress and develop. For example: principals are still less able to maintain school facilities; the principal has not been able to create a conducive school culture and atmosphere; principals are also less able to involve school personnel to be active in various activities at school; the principal has also not been able to direct the teachers to compose and develop the syllabus and lesson plans (Learning Implementation Plan); principals tend not to involve teachers in school committees for decision making. There are still many things that need to be addressed from the leadership of the principal. it is the author's interest to reveal how the ideal type of leadership figure is?